2004
DOI: 10.1598/rt.58.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Read‐Alouds: Is There a Common Set of Implementation Practices?

Abstract: Read‐alouds are a common component of literacy instruction. However, research on the method for providing read‐alouds is limited. To determine if there was a common set of implementation practices, the authors examined the read‐aloud practices of 25 teachers who were nominated by their administrators as experts. From these data, the authors identified several factors common to read‐alouds. The authors then observed 100 additional teachers to determine how common each of these factors were in read‐alouds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
0
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 8 publications
3
98
0
11
Order By: Relevance
“…For the young child, an interactive read aloud is an important method for learning about the conventions of texts that ultimately lead to independent reading. An interactive read aloud consists of a teacher selecting books that meet students' interests as well as their social and developmental levels, modeling fluent reading, and encouraging students to contribute in active ways (Barrentine 1996;Fisher et al 2004;Pantaleo 2007).…”
mentioning
confidence: 99%
“…For the young child, an interactive read aloud is an important method for learning about the conventions of texts that ultimately lead to independent reading. An interactive read aloud consists of a teacher selecting books that meet students' interests as well as their social and developmental levels, modeling fluent reading, and encouraging students to contribute in active ways (Barrentine 1996;Fisher et al 2004;Pantaleo 2007).…”
mentioning
confidence: 99%
“…Read-alouds are often conducted with a focus on strategy instruction (Fisher et al, 2004) or comprehension instruction that promotes the understanding of story elements, such as characters, plot, theme, or events (Oullette et al, 1999). Rather than look solely at textual analysis as a way of understanding literature, some researchers have suggested that literary understanding encompasses a rich variety of responses, as children bring together personal, social, and cultural responses to classroom discussions (Sipe, 2008) and express meaning in multimodal ways (Adomat, 2009).…”
Section: Read-aloudsmentioning
confidence: 99%
“…We would like to see read-alouds every day, in every class! We expect that our credential candidates can demonstrate competencies in delivering read-alouds that are aligned with the content of the class and that use quality, authentic literature (for information on the components of read-alouds, see Fisher, Flood, Lapp, & Frey, 2004).…”
Section: Teach Students Strategies For Reading and Writing Increasingmentioning
confidence: 99%